Oceans and Lakes: Byron's Interactions. Issue 2 (December 2019) - Beatty, Bernard
Abstract : The article distinguishes between the cult of imaginative fusion associated with many Romantic writers and Byron's imaginative attention to multiple kinds of interactions. Byron is interested in the transitions from consciousness based on inter-human relations to a consciousness empty of all content and relationship, to a different kind of consciousness based on relationship and interaction with non-human life forms. This article explores interactions between human and non-human beings, different social or entitative classes, between men and women, matter and spirit, living and dead, and writers and readers. Byron sees this as attention to the unlimited play of oceans rather than the confined stillness of lakes.